Effect of time of Planting on the Growth and Flowering of Popular Bedding plants - Rose Mary Joice (Department of Horticulture, College of Agriculture, 1990)
A field experiment was conducted at the college of Agriculture, Vellayani during 1988-89 to study the effect of time of planting on the growth and flowering of popular bedding plants namely Marigold, Zinnia , Balsam, Phlox and Salvia. For reasons not absolutely known stand of adequate size could not be obtained for Salvia and Phlox and hence the two crops were not carried over through the remaining part of experiment.